Financial Management Transformation of Islamic Boarding Schools through Break Even Point Analysis - Muhammad Ilmi Najib; Muhammad Bisri Ihwan (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study analyzes the application of Break Even Point in transforming financial management at Pondok Pesantren Salaf Darussalam Rejoagung Banyuwangi and its implications for institutional independence and sustainability. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation from January to June 2025. Analysis employed the interactive model of Miles and Huberman, with data validity ensured through source triangulation, member checking, and intensive researcher involvement. Findings reveal that Break Even Point emerged from the critical awareness of pesantren leaders regarding financial uncertainty traditionally dependent on donations, functioning as both an objective instrument and a metaphorical “map and compass” guiding financial navigation without neglecting spiritual values. The contextualization of fixed, variable, semi-variable, and non-cash costs highlighted ethical dilemmas in monetizing internal resources. Break Even Point fostered independence through digital financial management, business unit development, sustainable operational planning, and strategic decision-making. The study concludes that Break Even Point serves not only as a financial tool but also as an institutional catalyst bridging modern accountability with pesantren spirituality.